Sport4Change : adapting to COVID-19 through innovation - McSweeney, Mitchell (SAGE Business Cases., 2021)
The case explores how Sport4Change will adapt its sport-for-development (SFD) programs in response to the current uncertainty presented by COVID-19. Being able to innovate program operations, implementation, and delivery is key to the success and long-term sustainability of Sport4Change, and changing program strategies needs to be done correctly given the organization's varying locations around the world. Making such decisions requires consideration of the various contexts in which Sport4Change works, understanding diverse options to implement SFD through technological or remote means, and aligning remote delivery and operations with each SFD location and their in-person program focus and goals in order to come up with solutions to ensure SFD remains impactful during COVID-19.